Examining cooperative sustainable growth rates: who is growing broke? - Smart, Nathan (Kansas State University, 2018)
Many cooperatives are growing at an exceptional rate. Cooperative growth has been fueled by producer consolidation, a highly competitive marketplace and new opportunities through rising global demand. However, growth at an exceptional rate may be unsustainable and could potentially cause significant financial stress. Cooperatives could get so caught up in growing that they could create problems, or “grow broke.” The sustainable growth rate (SGR) is a financial metric used by many businesses to address this potential growth problem and can be used by cooperatives to ensure their long-run success. Thus, the objective of this research is to better understand the SGRs of cooperatives, provide baseline SGRs, determine key attributes of higher growth rate cooperatives and key indicators of SGR changes. The SGR relates to the retained earnings growth of a cooperative. Boosting a cooperative’s retained earnings can be done by manipulating the four levers of growth to attain higher retained earnings. These financial decisions will also boost a firm’s SGR. Increased retained earnings lends more flexibility to expand through organic growth or acquisitions. The SGR provides little information if not compared to actual growth results across time and across industry standards. Actual growth rates are measured by the year-over-year change in sales as Higgins (1977) details. By determining the difference between actual sales and the SGR, the sustainable growth challenge (SGC) is found. The SGC is a straightforward way to see how far a firm is straying from the SGR and, over time, see where the correction was made to converge to the SGR. If a business has a negative SGC, then actual growth rates exceeded SGR, which means outside financing is necessary to fund growth. If SGC is positive, then the firm is not meeting their growth target and potentially not capturing their full value for their owners. (Higgins, 1977) A seemingly unrelated regression approach is used to analyze the interrelationships of the four levers of growth using panel data from the CoBank Risk Analyst database of Midwest cooperatives’ financial and operating information. Breaking cooperatives into “large” and “small” designated groups will aids determining factors of boosted retained earnings. The cooperatives are also grouped based on regional location as well as the percentage that farm supply sales make up total sales. The drivers of SGR in today’s cooperatives will be examined—higher profit margin, or lower patronage—to determine which factors are more practical for specific cooperative size and type. In addition, the size of cooperative that faces the largest SGC and whether that sector also has a higher or lower SGR is of interest to this research. (“CoBank Risk Analyst Database,” 2017) Econometric results identify the most useful levers to boost the SGR, change the SGC or both. Profit margin is the key driver of sustainable growth; however, operating efficiency and leverage are key factors as well. When a growth challenge is present, leverage is most often used and the biggest contributor to changes in the SGC. Cooperatives of each size, location and region grow and are affected by growth challenges. This study will help cooperative directors understand the financial decision repercussions on growth and growth challenges.
Keywords: Cooperative; SGR; Growth; Earnings; Rate; Finance